2000
DOI: 10.1074/jbc.m909220199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Aspartate Transcarbamoylase fromMethanococcus jannaschii

Abstract: The genes from the thermophilic archaeabacterium Methanococcus jannaschii that code for the putative catalytic and regulatory chains of aspartate transcarbamoylase were expressed at high levels in Escherichia coli. Only the M. jannaschii PyrB (Mj-PyrB) gene product exhibited catalytic activity. A purification protocol was devised for the Mj-PyrB and M. jannaschii PyrI (Mj-PyrI) gene products. Molecular weight measurements of the Mj-PyrB and Mj-PyrI gene products revealed that the Mj-PyrB gene product is a trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…The influence of temperature on the reaction rate was determined from a series of aspartate saturation curves obtained at different temperatures. The Arrhenius plot of log V max against 1/T (not shown) is linear, with a calculated activation energy (E a ) of 53.6 kJ/mol, a value comparable with those determined for ATCases from Pyrococcus abyssi (34), Methanocaldococcus jannaschii (33), and E. coli (35). The presence of the E. coli ATCase allosteric effectors CTP, UTP, and ATP at 5 mM had no effect on the activity of the enzyme.…”
Section: Identification and Sequence Analysis Of A Aeolicus Atcase-mentioning
confidence: 62%
“…The influence of temperature on the reaction rate was determined from a series of aspartate saturation curves obtained at different temperatures. The Arrhenius plot of log V max against 1/T (not shown) is linear, with a calculated activation energy (E a ) of 53.6 kJ/mol, a value comparable with those determined for ATCases from Pyrococcus abyssi (34), Methanocaldococcus jannaschii (33), and E. coli (35). The presence of the E. coli ATCase allosteric effectors CTP, UTP, and ATP at 5 mM had no effect on the activity of the enzyme.…”
Section: Identification and Sequence Analysis Of A Aeolicus Atcase-mentioning
confidence: 62%
“…The enzymes from enterobacteria are dodecameric holoenzymes composed of two different polypeptides which are inhibited by CTP and UTP and activated by ATP. The same architecture was found for other bacterial ATCases, like that from Methanococcus janaschii, although the M. janaschii enzyme exhibited few regulatory properties (32). Some bacterial and eukaryotic ATCases are part of a multifunctional enzyme containing carbamoylphosphate synthetase and/or dihydroorotase activity, among them the enzyme of S. cerevisiae, which is inhibited by UTP (87).…”
Section: Atcase Activitiesmentioning
confidence: 76%
“…The similarity between the association of the two catalytic trimers in the present structure and in the monoclinic form in different crystalline environments indicates that this arrangement is stable. However, size-exclusion chromatography studies have shown that the catalytic subunits exist as isolated trimers in Tris solution (Hack et al, 2000). It is possible that the association we observe in the crystalline state occurs at high concentrations of the protein and/or in the presence of ammonium sulfate.…”
Section: Description Of the Structurementioning
confidence: 97%
“…The M. jannaschii catalytic trimer was prepared following the procedure of Hack et al (2000) from E. coli strain EK1911 which has a deletion in the pyrBI region of the chromosome and contains the plasmids pEK406 coding for the M. jannaschii catalytic chain and pSJS1240 (Kim et al, 1998) coding for rare archaeal tRNAs. The gene for the M. jannaschii catalytic chain is not associated with any tags in pEK406.…”
Section: Protein Preparation and Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation